Anaesthesia in Elective Surgery and its Outcome - Khot, Dr. Sanjay; Verma, Dr. S. R. (International Journal of Innovative Research in Medical Science, 2018)
INTRODUCTION Anaesthesia is classified into two main techniques general anaesthesia (GA) in which gaseous and/or intravenous drugs achieve central neurological depression, and regional anaesthesia, in which drugs are administered directly to the vicinity of spinal cord or nerves to locally block afferent and efferent nerves. The anaesthesiologist is the medical specialists who can evaluate the risk associated with the anaesthesia discuss these risks with the patient and surgeon to manage them intraoperative. Now a day anesthesia is no longer limited to the operation room but it a perioperative care . The presence of comorbid conditions in surgical patients is significant factors in preoperative morbidity and mortality risk assessment . The current practices in anesthesia include complete valuation of risks, control costs, allocate resources, and postpone surgery until interventions improve risk .